Effect of Molecular Rotational Degrees of Freedom on Mechanical and Thermodynamic Properties of Solid Methane at Temperatures above 50 K. (7th October 2014) - Leont'eva, Antonina V.; Prokhorov, Andrew Yu.; Zakharov, Anatoly Yu.; Erenburg, Alexander I.
Abstract : The paper presents an analysis of extensive data set of mechanical, structural, thermophysical, and spectral properties of solid methane in the temperature interval 0.5 ·  T tr – T tr ( T tr is the triple point temperature) under equilibrium vapor pressure. It is shown that the anomalies of the studied properties (or lack of reliable data) at temperatures 60–70 K have been observed in the body of the reviewed papers. We proposed that the observed anomalies are due to a transition between classical and quantum regimes of collective rotational degrees of freedom of methane molecules in this temperature interval.